Mikrofertigungstechnologien und ihre Anwendungen - ein theoretischer und praktischer Leitfaden - Brunet, AdrienMüller, TobiasScholz, Steffen (KIT Scientific Publishing, 2017)
This book collates contributions from within the fields of micro-manufacturing technologies and engineering, and complements the online training platform developed by the MIMAN-T consortium. This book primarily targets technicians and prospective professionals as well as student operating within the sector and aims to serve as an effective tool to facilitate the translation of micro-manufacturing technologies into tangible industrial benefits.